The Influence of Profitability on Stock Prices in the Financing Sector Companies Listed on the Indonesia Stock Exchange - Akbar, Rayyan Taufik; Wulandari, Retno; Irfan Rizki, Muhammad (Indonesian Journal Publisher, 2025)
Profitability serves as a crucial measure in evaluating a company's financial health, especially within the financing industry listed on the Indonesia Stock Exchange (IDX). This research investigates the impact of Return on Assets (ROA) on the stock prices of financing firms. A quantitative approach was utilized, applying simple linear regression analysis. Data were sourced from annual reports and the official IDX website for the 2020–2023 period, with 24 data points selected using purposive sampling. Classical assumption testing confirmed that the model satisfied the conditions for normality and homoscedasticity. The analysis revealed a significant positive relationship between ROA and stock prices, with a coefficient of 100.070 and an R² of 0.556, meaning ROA accounts for 55.6% of stock price variation. The findings are in line with signaling theory, highlighting ROA as an indicator of company efficiency and stability during uncertain economic conditions. The study suggests that firms should enhance asset utilization to sustain profitability, investors should consider ROA in their evaluations, and future studies should integrate additional financial metrics for a broader analysis.